Medieval Prisons: Between Myth and Reality, Hell and Purgatory - Geltner, Guy (History compass, 2006)
When were medieval prisons founded? What was life inside them like? How did contemporary observers perceive them? Addressing such questions, this article brings together over a century of scholarship that undermines the traditional dating of the prison's "birth," sheds light on the tolerable realities of medieval captivity, and identifies a range of contemporary interpretations of prison life and spaces.